Changes in the bacterial community structure in two-stage constructed wetlands with different plants for industrial wastewater treatment - Calheiros, Cristina S.C. (2010)
This study focused on the diversity of bacterial communities from two series of two-stage constructed wetlands (CWs) treating tannery wastewater, under different hydraulic conditions. Series were separately planted with Typha latifolia and Phragmites australis in expanded clay aggregates and operated for 31 months. The effect of plant species, hydraulic loading and unit stage on bacterial communities was addressed through bacterial enumeration and denaturating gradient gel electrophoresis (DGGE). Diverse and distinct bacterial communities were found in each system unit, which was related in part to the type of plant and stage position (first or second unit in the series). Numerical analysis of DGGE profiles showed high diversity in each unit with an even distribution of species. No clear relation was established between the sample collection time, hydraulic loading applied and the bacterial diversity. Isolates retrieved from plant roots and substrates of CWs were affiliated with c-Proteobacteria, Firmicutes, a-Proteobacteria, Sphingobacteria, Actinobacteria and Bacteroidetes. Both series were effective in removing organic matter from the inlet wastewater, however, based on batch degradation experiments it seems that biodegradation was limited by the recalcitrant properties of the wastewater